(untitled) (مجلة جامعة دمشق للعلوم الاقتصادية و السياسية, 2026)
This study aimed to identify the role of digital transformation in supporting brainstorming sessions in auditing. It is a field study that relied on the descriptive analytical approach and used the questionnaire as a tool to collect data and then test its hypotheses using the SPSS statistical analysis program. The study community was represented by auditors working in auditing offices and companies accredited to audit the accounts of entities subject to the supervision of the Syrian Securities and Markets Commission for the year 2024, which numbered (23) auditing offices and companies, while the study sample consisted of (95) auditors. The study reached a consensus among auditors on the existence of a significant relationship between the role of digital transformation and its technologies in supporting brainstorming sessions in auditing, especially with regard to developing auditors’ performance and skills by increasing communication and interaction methods between auditors, exchanging ideas, and benefiting from their previous experiences in understanding the problem at hand, audit risks, and methods of evaluating them, on the one hand, and by collecting the largest amount of appropriate evidence and analyzing it more accurately, on the other hand, through speed in completing and implementing the operations required to be analyzed and processed, expanding auditing and testing operations, and diversifying sources of evidence collection, in addition to processing and analyzing huge amounts of information and data and storing them for long periods of time so that they can be easily retrieved during the session.